BUSINESS FEASIBILITY STUDY OF GLUTEN-FREE CHOUX WITH NUSANTARA TASTE â€œPUFF YOU!â€ - Gumarus, Bryan Alexander; Juliana, Juliana (AGUSPATI Research Institute, 2022)
Puff You! is a Café Specialize Choux located in Greenville, West Jakarta. Puff You! offers the main product Choux gluten-free with the taste of the Indonesia flavors which can provide an opportunity for consumers who cannot eat desserts containing gluten. Puff You! is not only selling dessert choux but also equipped with various types of coffee, tea, and snacks. Puff You! target market are people who from 15 years and above who live in West Jakarta, but it is possible if people who live outside DKI Jakarta visit Puff You! The main purpose of this business feasibility study is to test and assess whether Puff You! can be stated as a business idea that is feasible to run into a real business, seen from various aspects, such as market and marketing aspects, operational aspects, organizational and human resources aspects, and financial aspects. The data in this business feasibility study uses a purposive sampling technique with primary data collection by observation and distribution of online questionnaires with 384 respondents, as well as secondary data (internet and books). Café Puff You! feasible and profitable to run as a real business Keywords: Business Feasibility, Café, Choux, Gluten-free, Nusantara Taste